Clinical characteristics and outcomes of ischemic stroke patients during Ramadan vs. non-Ramadan months: Is there a difference? - Alotaibi, Naser; Aldriweesh, Mohammed A.; Alhasson, Muath A.; Albdah, Bayan A.; Aldbas, Abdulaziz A.; Alluhidan, Waleed A.; Alsaif, Sultan A.; Almutairi, Faisal M.; Alskaini, Mohammed A.; Al Khathaami, Ali M. (Frontiers in Neurology, 2022)
Abstract Objectives: To study the clinical characteristics and outcomes of patients experiencing an ischemic stroke during Ramadan versus non-Ramadan months in a tertiary academic center in an Islamic country. Methods: We retrospectively reviewed all patients with ischemic stroke (IS) in Ramadan and non-Ramadan months for four consecutive years (February 2016–June 2019). All demographics, vascular risk factors, laboratory results, modified Rankin Scale (mRS) at admission and discharge, National Institute Stroke Scale (NIHSS), and in-hospital complication data were collected for all patients. Results: One thousand and fifty-eight patients were included (non-Ramadan, n=960; during Ramadan, n=98). The mean age during Ramadan was 59±13 years. Most non-Ramadan IS patients during Ramadan were male (68.5%; 57.1%, respectively). There was no statistical difference in vascular risk factors and medical history between the two groups. However, Ramadan patients had higher median NIHSS scores at discharge (p=0.0045). In addition, more ICU admissions were noted among Ramadan patients (p=0.009). In the gender-specific analysis for Ramadan patients, we found a statistically significant difference in smoking and urinary tract infection (p=0.006, p=0.005, respectively). Conclusion: Based on our results, there was no difference, in general, between patients with IS during Ramadan and non-Ramadan months. However, IS patients during Ramadan had higher NIHSS scores at discharge and more ICU admissions. Last, we suggest future studies with larger sample sizes, longer duration, and including all types of strokes.